IMPLEMENTASI MEDIA PLATFORM QUIZIZZ DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PAI - Romdhon Pamungkas, Muhammad Fajar; Anshori, Sholihul (EL-Islam, 2025)
Abstract: Education is a vital element that deserves to be prioritized due to its considerable impact on both individual development and the long-term advancement of society. One fundamental aspect within the educational field is Islamic Religious Education (PAI), which not only serves to convey knowledge about Islamic teachings but also plays a role in shaping daily behavior through the internalization of Islamic values. Its ultimate aim is to cultivate students who possess noble character and morals.In the school learning context, implementing PAI requires innovative methods to enhance students’ engagement with the material presented. A relevant innovation in today’s digital era is the use of platform-based learning technologies such as Quizizz.This study aims to: (1) describe how the Quizizz platform is applied in teaching PAI to eighth-grade students at SMP Dwi Dharma Mojowarno in Jombang; and (2) explain how the use of this platform contributes to increasing students' interest in the PAI subject. The research employs a qualitative approach through a case study method. Data collection techniques include observation, in-depth interviews, and documentation, involving the principal, PAI teachers, and eighth-grade students as participants.Data analysis was conducted through three systematic stages: data reduction, data presentation, and drawing conclusions. The findings reveal that the use of Quizizz in PAI learning for eighth graders at SMP Dwi Dharma Mojowarno has been implemented effectively across three main stages: planning, execution, and evaluation. The platform is considered suitable due to its alignment with the learning materials, ease of access for students, support from teachers’ technological proficiency, and adequate supporting facilities. Furthermore, the integration of Quizizz significantly enhances students' learning interest, as evidenced by increased enthusiasm, attention, and active participation throughout the learning process.